Experimental performance of perforated glazed solar air heaters and unglazed transpired solar air heater - Vaziri, Roozbeh; İlkan, Mustafa; Egelioğlu, Fuat (Solar Energy, Elsevier, 2015)
In this study, the thermal performances of perforated glazed solar air heaters (PGSAHs) having different inner collector colors and a black colored unglazed transpired solar air heater (UTSAH) were investigated experimentally. Two PGSAHs having perforated plexiglas glazing and different inside bottom colors were constructed. The third solar air heater was a UTSAH where the top cover was black colored perforated sheet metal. The diameters of the holes on the plexiglas covers and sheet metal cover were 3 mm and the pitch distance was 30 mm. No absorber plates were used in PGSAHs, where perforated metal cover is the absorber plate in the UTSAH. Added fans draw ambient air into the collectors through the perforated plexiglas in the PGSAHs. Similarly an added fan draws ambient air into the collector through the perforated metal in the UTSAH. The air mass flow rate was varied between 0.017 kg/s and 0.036 kg/s. The highest efficiencies were achieved at mass flow rate of 0.036 kg/s. The highest values of efficiency for black, green, blue, red, violet, light yellow and white PGSAHs were, 85%, 84%, 76%, 65%, 61%, 54%, and 55% respectively, while at the same mass flow rate the maximum value of efficiency for the UTSAH was 50%.
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI (with DOI: 10.1016/j.solener.2015.06.043) and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: Perforated glazed solar air heater; Transpired solar air heater; Thermal efficiency; Collector colors